A new genus and species of Cicadellini (Insecta: Hemiptera: Cicadellidae: Cicadellinae) from the Brazilian Atlantic Forest - Nathalia H. Pecly; Victor Quintas; Alexandre C. Domahovski; Rodney R. Cavichioli; Gabriel Mejdalani (European Journal of Taxonomy, 2024)
The remarkable sharpshooter Prodigiella silvanoi gen. et sp. nov. is described and illustrated (including the external form, color, male and female terminalia) from the Atlantic Forest of southern and southeastern Brazil (states of Paraná and Rio de Janeiro). The new genus can be distinguished from other Neotropical genera of the Cicadellini by a combination of various morphological features, including an asymmetrical aedeagus with a bifid shaft and peculiar basal and apical processes and ovipositor valvula II distinctly expanded beyond basal curvature, its dorsal margin with 35–40 teeth, and ventral margin without preapical prominence. A discussion comparing Prodigiella with superficially similar taxa of the genera Macugonalia Young, 1977, Ruppeliana Young, 1977, and Versigonalia Young, 1977 is provided. The discovery of this peculiar new genus indicates that much collecting work in the remaining parts of the Atlantic Forest is clearly and urgently needed.